Wisata Pulau Tilan Dari Festival Menuju Ekowisata Di Desa Wisata Rantau Bais - Amrita, Devita Candra; Amady, M Rawa El; Hidir, Achmad (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
This study discussed tourist destinations in Tilan Island, which was built under the initiative of the local youth through festival tourism. The tourist destination has been positively responded to by visitors whose number keeps increasing each year, and Kepenghuluan Rantau Bais has been recognised as a Tourism Village. Tourism in Tilan Island persistently transforms from festival tourism to regular tourism, starting from its opening every Saturday and Sunday. This study is a qualitative study that uses the ethnography method where the researcher lived for two months in Kepenghuluan Rantau Bais. The data was obtained using participative observation and in-depth interviews with an appointed informant who has a wide knowledge on tourism in Tilan Island. This research found that not all tourism potential in Tilan Island and Rokan River are explored to become tourist activities. The said destination has the potential to be developed. Not just because of the natural potential, but also because the locals are very enthusiastic in supporting this program. Tourism in Tilan Island has been known all the way to Pekanbaru, Duri, Dumai, and North Sumatra. This study contributes towards the tourism field of study using the ethnography approach. This study can be used by tourism managers and local governments to further develop tourism in Tilan Island and similar tourist destinations in other villages. Keyword: Festival Tourism, Regular Tourism, Ecotourism, Tourism Development